Assembling Si2BN nanoribbons into a 3D porous structure as a universal anode material for both Li- and Na-ion batteries with high performance. Issue 37 (18th September 2020) - Younis, Umer; Muhammad, Imran; Wu, Wei; Ahmed, S.; Sun, Qiang; Jena, Puru
Abstract : A porous 3D-Si2 BN structure is assembled from the nanoribbons of a 2D monolayer Si2 BN sheet, and is meta-stable energetically while being stable chemically, dynamically and thermally, exhibiting high theoretical capacity and low energy barriers for both Li and Na ions. Abstract : The development of anode materials is critical to the success of sodium ion batteries (SIBs). Because of the size difference between Li and Na, the commercial anode material graphite in Li-ion batteries does not work for Na-ion batteries. Thus, it will be ideal if some universal anode materials could work for both Li- and Na-ion batteries with high performance. Inspired by a recent study on the high performance of a 2D-Si2 BN sheet as an anode material for Li-ion batteries, we design a three dimensional (3D) porous structure by using the nanoribbons of a Si2 BN sheet as building blocks. Based on the state-of-the-art ab initio calculations, we find that the resulting 3D porous Si2 BN structure is stable chemically, dynamically and thermally, exhibiting a high specific capacity of 512.42 (341.61 mA h g −1 ), a low voltage of 0.27 V (0.15 V), a small volume expansion of 2.5% (2.7%), and a low migration energy barrier of 0.44 eV (0.19 eV) for Li- (Na-) ion batteries. These intriguing features, together with the light mass and rich abundance of Si, B and N, suggest that the 3D porous Si2 BN structure is a promising candidate for the anode material of both Li- and Na-ion batteries.